(untitled) (Research, Society and Development, 2024)
Introduction: The Crew Resource Management (CRM), translated from the English language as team resource management, is a training that seeks to improve non-technical skills, such as leadership, communication, interpersonal relationships, situational awareness, decision making, fair culture and error management. Objective:This work aims to show how the CRM, being a pedagogical tool applied to aviation, not only can, but is increasing the level of security within hospitals, surgical centers and places where security of the patient must be high. It is hoped that this manuscript will be a source of knowledge on the subject of patient safety and inspiration for health professionals. Methodology:This is an integrative literature search, of a qualitative and exploratory nature, analyzing articles published in indexed journals that deal, in specific databases, with the topic of CRM, as a pedagogical tool applied to aviation in Medicine between the years of 1978 and 2018. This step was divided into six parts, namely identification of the theme, designation of inclusion and exclusion criteria, extraction of information, evaluation of studies, discussion of results and presentation of the review. Results: In the end, 15 articles were selected that talk about the application of CRM in Medicine, which served as the basis for the construction of this work.Conclusion: Patient safety can only grow and improve with the implementation of training in resource management. team for medical professionals, whether nurses, assistants, anesthesiologists, residents and/or experienced surgeons.